DIAGNOSIS AND TREATMENT OF CARDIAC MYXOMA - Y. V. Zheltovskiy (Scientific Сentre for Family Health and Human Reproduction Problems, 2017)
Cardiac tumors are extremely rare pathologies with polymorphic clinical presentation, mainly founded in autopsy, and accidentally in cardiac surgery. Primary tumors of the heart are detected in 0.002-0.05 cases of autopsies, and 75 % of the tumors are the benign ones. Cardiac myxoma is the most frequent tumor of the heart. It can be localized in any chamber, but more often occurs in the left atrium. A pedunculated myxomas prolapse into mitral orifice, obstructing outflow from left atrium and inflow to left ventricle in diastole. Microscopically myxomas can have slimy, rigid, lobed or loose structure. Myxomas with loose consistency are most dangerous in occurrence of systemic embolism. Also, tumors can locate in ventricle or in several heart chambers. Most of tumors has a peduncle, a fibrous-vascular stalk from 4 to 8 cm in diameter. In 93 % cases myxomas are the single chamber tumors, but they can be biatrial, and grow in several chambers of the heart, thus, are the multiple primary tumors. The symptoms are of widely varied character and depend on the size and localization of the tumor. Now, because of advances in diagnostic, the frequency of myxoma detection is annually increasing, counting from 0.5 to 2.3 cases per 1 million people. The group of 70 patients aged from 19 to 77 with morphologically confirmed myxomas was analyzed. Surgical intervention is the only way to treat myxoma. The case described in the article presents a large myxoma, almost completely filling left atrium with mitral orifice occlusion. Routine echocardiography facilitated a timely diagnosis, and required treatment was performed.